2017
DOI: 10.1007/s10495-017-1370-6
|View full text |Cite
|
Sign up to set email alerts
|

Augmenter of liver regeneration regulates autophagy in renal ischemia–reperfusion injury via the AMPK/mTOR pathway

Abstract: Autophagy may have protective effects in renal ischemia-reperfusion (I/R) injury, although the underlying mechanisms remain unclear. Augmenter of liver regeneration (ALR), a widely distributed multifunctional protein that is originally identified as a hepatic growth factor, may participate in the process of autophagy. To investigate the role of ALR in autophagy, ALR expression is knocked-down in human kidney 2 (HK-2) cells with short hairpin RNA lentivirals. Then, the level of autophagy is measured in the shRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Phosphorylation of AMPKα on threonine 172 (pT172) is required for full activation. Recent studies have reported that AMPK is the main initiator of stress‐triggered autophagy, which works through suppressing mTOR by activation of tuberous sclerosis complex 2 and direct phosphorylation of mTORC1 or unc‐51 like autophagy activating kinase 1 . In our study, we showed that GSK3β inhibition induces the phosphorylation of AMPK both in liver I/R and in primary hepatocyte H/R, as well as suppression of mTOR activity.…”
Section: Discussionsupporting
confidence: 63%
“…Phosphorylation of AMPKα on threonine 172 (pT172) is required for full activation. Recent studies have reported that AMPK is the main initiator of stress‐triggered autophagy, which works through suppressing mTOR by activation of tuberous sclerosis complex 2 and direct phosphorylation of mTORC1 or unc‐51 like autophagy activating kinase 1 . In our study, we showed that GSK3β inhibition induces the phosphorylation of AMPK both in liver I/R and in primary hepatocyte H/R, as well as suppression of mTOR activity.…”
Section: Discussionsupporting
confidence: 63%
“…When activated by certain stress, AMPK regulates sugars and fatty acids that are good or detrimental to the heart. For example, targeting AMPK phosphorylation is known to protect against ischemia reperfusion-induced injury [1,2]. The mammalian target of rapamycin complex 1 (mTORC1) has a central role among the intracellular signal transduction pathways adapting growth, metabolism and aging [3].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that tubule-specific c-met signaling plays an essential role in renal protection due to its proliferative, antiapoptotic, and anti-inflammatory properties. [71][72][73] Consistently, HGF/c-met attenuates renal injury and inflammation while accelerating repair after glycerol-induced AKI. 74 IGF and IGFBPs in AKI IGF, a peptide growth factor that is secreted by the collecting duct of the adult kidney, binds with IGF1R and phosphorylates insulin receptor substrate proteins, thereby initiating downstream pathways, including PI3K-Akt-mTOR, to participate in the regulation of cell proliferation and apoptosis 75,76 (Fig.…”
Section: Egf and The Egf Receptor In Akimentioning
confidence: 84%